"New Uzbekistan: Social State And The Dignity Of Humanity" - Anarbayev Jakhongir Botir ugli (Periodica Journal, 2025)
The article reflects the formation of the New Uzbekistan as a social state and approaches aimed at prioritizing human interests. It analyzes state policy aimed at improving the well-being of human life through social protection, economic development, and education and healthcare systems.
Keywords: Social state; human dignity; human interests